2018
DOI: 10.30937/2526-6314.v2n3.id58
|View full text |Cite
|
Sign up to set email alerts
|

Why woman run? Motivations for running in a half-marathon among female local runners and sport tourists

Abstract: The purpose of the study was to examine the motivations to participate in a half-marathon among womenlocal runners and sport-touristsand also to evaluate the differences between these two groups of respondents. Most of the research concerns motivation to run among men. With the increase in the popularity of mass running events, the question what encourages women to engage in physical activity, especially outside their everyday place of residence, becomes very important now. The sample comprised 214 women that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
2
10
1
Order By: Relevance
“…Such factors accord with previous research, but not necessarily in that order of importance [14,15]. In another study [17], long-distance runners stated that they were driven by the desire to experience strong emotions, have fun, and to enjoy the atmosphere of the sporting event.…”
Section: Introductionsupporting
confidence: 87%
“…Such factors accord with previous research, but not necessarily in that order of importance [14,15]. In another study [17], long-distance runners stated that they were driven by the desire to experience strong emotions, have fun, and to enjoy the atmosphere of the sporting event.…”
Section: Introductionsupporting
confidence: 87%
“…The latter gather thousands of people with different levels of skill who are keen to run such a distance ( Buning and Walker, 2016 ). Due to this popularity, a wide-ranging approach has analyzed these mass sports events, in an attempt to describe, among other aspects: the physical health benefits of running ( Hulteen et al, 2017 ; Oja et al, 2017 ; Mujika-Alberdi et al, 2018 ; Kozlovskaia et al, 2019 ); psychological benefits and mental change ( Mazyarkin et al, 2019 ), finding, for instance, that marathon runners’ mental health was better than that of non-athletes ( Raglin, 2007 ; Boudreau and Giorgi, 2010 ); endurance running performance-related research ( Ferrer et al, 2015 ); social, tourism, and leisure-related research ( Shipway and Jones, 2007 ; Waśkowski, 2011 ; Nowak and Chalimoniuk-Nowak, 2015 ; Summers et al, 2016 ; Malchrowicz-Mośko and Rozmiarek, 2018 ; Malchrowicz-Mośko et al, 2019 ), coaching-related research ( Malchrowicz-Mośko and Rozmiarek, 2018 ), and research involving analyzing psychosocial factors related to marathon running ( Summers et al, 2016 ); and psychological motivational characteristics of amateur or recreational runners ( Larumbe et al, 2009 ; Hammer and Podlog, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a great body of literature has tried to describe the reasons that have led athletes to take part in different sports endurance events, e.g., triathlons ( Croft et al, 1999 ; Wicker and Weimar, 2012 ; López-Fernández et al, 2014 ; Myburgh et al, 2014 ) and cycling events ( Lachausse, 2006 ; Heesch et al, 2012 ; Malchrowicz-Mośko et al, 2019 ). Apart from the previously cited sporting contexts, the Motivations of Marathoners Scale (MOMS), developed by Masters et al (1993) , has been used in different running contexts, such as adventure races ( Doppelmayr and Molkenthin, 2004 ), a 5 km running event ( Bell and Stephenson, 2014 ), half marathons ( Bell and Stephenson, 2014 ; Malchrowicz-Mośko et al, 2018 ), and ultramarathons ( Doppelmayr and Molkenthin, 2004 ; Frick, 2011 ; Malchrowicz-Mośko and Rozmiarek, 2018 ; Waśkiewicz et al, 2019a ), and for trying to distinguish athletes’ reasons for participation depending on the distance, comparing half marathon, full marathon, and ultramarathon runners’ reasons for participation ( Hanson et al, 2015 ). Other variables such as the type of event, traditional sports events vs. non-traditional sports events ( Buning and Walker, 2016 ), cause-related vs. non-cause-related endurance events ( Rundio et al, 2014 ), first-time marathoners’ motivations, and pre-race dropout reasons ( Havenar and Lochbaum, 2007 ) have been analyzed using the MOMS scale, in order to distinguish and understand what drives athletes to participate in those events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also studies on the motivational differences between local runners and sports tourists [32,33], and some papers have been published on university students and female local runners and female sports tourists. Test results indicated that local runners and sports tourists had similar motivations to run in mass events, albeit with some statistically significant differences [34,35].…”
Section: Introductionmentioning
confidence: 99%